Do pigeons (Columba livia) perceive object unity? - Ushitani, Tomokazu; Fujita, Kazuo; Yamanaka, Rie (Animal cognition, 2001)
Human infants perceive two rods moving in concert behind an occluder as one unitary rod. In four experiments we tested whether pigeons also perceive unity of objects. Pigeons were trained on a matching-to-sample task to discriminate between one unitary rod moving at a constant speed and two aligned rods moving together at the same speed. The latter stimulus was identical to the former except for a gap in the center. In experiment 1, we tested pigeons in probe trials in which a rectangle occluded the center of the sample rods, to see which comparison stimulus, the unitary rod or the aligned two rods, the subjects would match to the sample. Two of the three subjects pecked at the two rods significantly more often than at the unitary rod. In experiment 2, we trained the same pigeons to match the sample rods moving "in front of" the occluder. Pigeons persisted in matching two separate rods to the unitary rod moving in front of the occluder. In experiments 3 and 4, we used a parallelogram and an undulating shape as the occluder to alter the shape and the size of the portions above and below the occluder by the motion of the sample rods. Both subjects chose the two rods significantly more often than chance in experiment 3 and one of them did so in experiment 4. The results suggest that pigeons do not complete occluded portions even though the two elements move in concert. These negative results suggest that some alternative way of identifying objects may have evolved in pigeons.